TEACHING MEDIA IN EFL CLASSROOMS: WHAT ARE THEY AND WHY SELECT THEM ? - Kiki Andriani; Ardiana; Firman (FKIP Unismuh Makassar, 2022)
Teaching media are essential in the teaching and learning English. The use of appropriate media in teaching a new language will help teachers create more effective learning environment in the classrooms. Using a descriptive qualitative method, this study explores what kinds of teaching media used by the teachers in teaching English and what factors influencing English teachers’ selection of teaching media in the classroom. This study was conducted at SMP Unismuh Makassar, involving two English teachers who have worked there for several years. The researcher used interview and observation as instruments in data collection process. The data were analyzed using data reduction, data display and data verification. The results of the study show that the teachers make use of four kinds of media, namely graphic media such as textbook and picture, media video such as video, projected media such as Power Point and display media such as a board. In addition, the factors influencing the teachers’ selection of those media are time availability, media availability, students’ characteristics, and students’ needs